The Effects of Influencer Marketing and Flash Sale Discount Programs on the Purchasing Decisions of Generation Z Consumers in the Digital Era - Zaharuddin Zaharuddin; Supriyadi Supriyadi; Sri Wahyuningsih (Smart Society, 2026)
As businesses increasingly compete for the attention of Generation Z consumers in digital marketplaces, understanding whether purchasing decisions are driven more by social influence or promotional incentives has become a critical issue for developing effective marketing strategies. Although influencer marketing and flash sale discount programs are widely used in e-commerce, previous studies have predominantly examined these strategies separately, providing limited evidence regarding their relative association with Generation Z consumers’ purchasing decisions. This study aims to analyze the relationship between influencer marketing and flash sale discount programs and the purchasing decisions of Generation Z consumers in the digital era. A quantitative approach was employed using a survey method involving 192 students from the Faculty of Economics and Business at Mitra Bangsa University, selected through random sampling. Data were collected through questionnaires and analyzed using SmartPLS. The results indicate that influencer marketing has a path coefficient of 0.361 on Generation Z purchasing decisions, while flash sale discount programs have a path coefficient of 0.592. These findings demonstrate positive relationships between both variables and purchasing decisions, with the relationship between flash sale discount programs and purchasing decisions being relatively stronger than that of influencer marketing. This study contributes to expanding the understanding of factors associated with Generation Z consumers’ purchasing decisions by integrating influencer marketing and flash sale discount programs into a single research model.